2011
DOI: 10.1242/jeb.053801
|View full text |Cite
|
Sign up to set email alerts
|

Animal escapology II: escape trajectory case studies

Abstract: Summary Escape trajectories (ETs; measured as the angle relative to the direction of the threat) have been studied in many taxa using a variety of methodologies and definitions. Here, we provide a review of methodological issues followed by a survey of ET studies across animal taxa, including insects, crustaceans, molluscs, lizards, fish, amphibians, birds and mammals. Variability in ETs is examined in terms of ecological significance and morpho-physiological constraints. The survey shows that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
155
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(162 citation statements)
references
References 149 publications
7
155
0
Order By: Relevance
“…Turn direction variability was also reported for responses to visual (Chan and Gabbiani, 2013) and thermal (Shoemaker and Robertson, 1998) stimuli. Escape variability may be a way to preclude anticipation by predators (Card, 2012) and is a common strategy employed by many animals (Domenici et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Turn direction variability was also reported for responses to visual (Chan and Gabbiani, 2013) and thermal (Shoemaker and Robertson, 1998) stimuli. Escape variability may be a way to preclude anticipation by predators (Card, 2012) and is a common strategy employed by many animals (Domenici et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Away and towards responses are escapes with a rotation directed away from and towards the stimulus, respectively. A towards response does not necessarily imply that the final escape trajectory will be towards the stimulus, because an animal initially oriented at 170deg that makes a 20deg rotation towards the stimulus will end up having an escape trajectory of 150deg from the stimulus itself (Domenici et al, 2011). We note that, in contrast to the general convention adopted in this paper, some authors have based their definition of away and towards responses on the final trajectory (e.g.…”
Section: The Meaning Of Directionalitymentioning
confidence: 92%
“…whether prey escape by rotating their body away from or towards the threat. A theoretical framework for predicting escape trajectories is then presented, followed by a discussion of the emerging trends of escape trajectories in various animal taxa that is based on a survey of ET data from the literature in the accompanying paper (Domenici et al, 2011). We also consider taxon-specific physiology and ecology, the implications for the sensory and locomotor systems, the issue of context dependency and conclude with the significance of escape trajectories in terms of survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most prior research on optimal evasive responses by birds has focused on locomotion rather than sensory inputs (Hedenstrom and Rosen, 2001;Howland, 1974;Van den Hout et al, 2010;Weihs and Webb, 1984). A recent review of prey escape strategies has commented on the tendency of prey to double back and move toward the pursuing predator (Domenici et al, 2011), a strategy found to result in lower capture rates for owls (Shifferman and Eilam, 2004). Such prey maneuvers may be attempts to move out of the predator's high acuity visual field.…”
Section: Research Articlementioning
confidence: 99%